2007
DOI: 10.1097/nen.0b013e3181567c31
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of cAMP Phosphodiesterase PDE4B2 Expression in Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) in Lewis rats is the most widely used animal model for multiple sclerosis. Cyclic adenosine monophosphate (cAMP) has been associated with neuroinflammation. The aim of this study was to investigate the possible involvement of different cAMP-specific phosphodiesterase (PDE) isoenzymes by analyzing their expression in the brain of EAE rats. We found in the brain of EAE animals that there was a dramatic increase in the mRNA expression levels of the PDE4B isozyme det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…Upregulation of PDE4B2 mRNA expression was observed 2-3 days after the onset of the disease (day 15), and was significantly elevated in animals with ongoing EAE in the spinal cord and later spreading throughout the posterior brain areas, coinciding with previous results in rats (Reyes-Irisarri et al, 2007). The PDE4B protein presented a distribution pattern comparable to that observed for infiltrating cells in the EAE brain during disease (Brown and Sawchenko 2007) suggesting that these cells might express PDE4B2 at elevated levels.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Upregulation of PDE4B2 mRNA expression was observed 2-3 days after the onset of the disease (day 15), and was significantly elevated in animals with ongoing EAE in the spinal cord and later spreading throughout the posterior brain areas, coinciding with previous results in rats (Reyes-Irisarri et al, 2007). The PDE4B protein presented a distribution pattern comparable to that observed for infiltrating cells in the EAE brain during disease (Brown and Sawchenko 2007) suggesting that these cells might express PDE4B2 at elevated levels.…”
Section: Discussionsupporting
confidence: 73%
“…In the EAE model, amelioration of the clinical signs and delayed onset is observed after PDE4 inhibition with rolipram (Folcik et al, 1999;Moore et al, 2006;Sommer et al, 1995). The PDE4B gene has been related to the inflammatory response in mouse monocytes and macrophages (Jin et al, 2005a) and previous publications by our group have shown that the PDE4B mRNA splice variant PDE4B2 is upregulated in cellular infiltrates of EAE rat brains (Reyes-Irisarri et al, 2007). Furthermore, during innate inflammation the expression of both PDE4B2 and PDE4B3 mRNAs are altered (Johansson et al, 2011;2012b), suggesting a possible role of these enzymes in regulating the cytokine environment during neuroinflammation.…”
Section: Introductionmentioning
confidence: 90%
“…Besides CRE elements, the PDE4B2 promoter also contains an NF-κB canonical site [13, 39]. These isoforms regulate pro-inflammatory cytokine expression within inflammatory cells [13, 40, 42, 43]. The initial increases observed with these isoforms may be due to regulation through the NF-κB pathway within inflammatory cells, whereas the sustained increases may be through the cAMP pathway.…”
Section: Phosphodiesterase Regulation In Brain Traumamentioning
confidence: 99%
“…While acute morphine inhibits adenylate cyclase, chronic morphine and morphine withdrawal results in super activation of adenylate cyclase with a resultant increase in intracellular cAMP (Wang et al 2007). Several animal studies implicate elevated cAMP with persistent neuroinflammation (Ghavami et al 2006;Reyes-Irisarri et al 2007) and cAMP-reducing agents display a potent antiinflammatory effect in vivo and in vitro studies. Chronic morphine treatment of murine macrophages shows a biphasic response in LPS and Streptococcus pneumoniaeinduced proinflammatory cytokine synthesis ).…”
Section: Numerous Mechanisms By Which Mu-opioid Receptor Agonists Affmentioning
confidence: 97%